2021
DOI: 10.1063/5.0056674
|View full text |Cite
|
Sign up to set email alerts
|

Toward the predictive discovery of ambipolarly dopable ultra-wide-band-gap semiconductors: The case of rutile GeO2

Abstract: Ultrawide-band-gap (UWBG) semiconductors are promising for fast, compact, and energyefficient power-electronics devices. Their wider band gaps result in higher breakdown electric fields that enable high-power switching with a lower energy loss. Yet, the leading UWBG semiconductors suffer from intrinsic materials limitations with regards to their doping asymmetry that impedes their adoption in CMOS technology. Improvements in the ambipolar doping of UWBG materials will enable a wider range of applications in po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 102 publications
0
25
0
Order By: Relevance
“…GeO 2 exists primarily in two phases, that is, α-quartz (hexagonal structure) and rutile (tetragonal) phases. Both the polymorphs of GeO 2 fall into the class of UWBG semiconductors with a band gap significantly higher than 4 eV, while conventional semiconductors are in the range of 0.5–4.0 eV . With higher carrier mobility and better ambipolar dopability, GeO 2 can be a perfect material of choice for homoepitaxially grown p - n junction-based next-generation efficient electronic and optoelectronic devices. , GeO 2 is theoretically anticipated to have a higher intrinsic phonon-limited thermal conductivity (37 W m –1 K –1 along the a direction and 58 W m –1 K –1 along the c direction at 300 K) than others which belong to the same class of UWBG semiconductors . Previous reports have theoretically predicted a high p and n Baliga Figure of Merit for the GeO 2 rutile phase, which can be beneficial while designing power devices with higher block-in voltage with improved on-set carrier conductivity. , Despite the ideal properties for various applications, GeO 2 suffers from the lack in ability to conveniently synthesize nanostructured thin films with a controlled microstructure and crystal phase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GeO 2 exists primarily in two phases, that is, α-quartz (hexagonal structure) and rutile (tetragonal) phases. Both the polymorphs of GeO 2 fall into the class of UWBG semiconductors with a band gap significantly higher than 4 eV, while conventional semiconductors are in the range of 0.5–4.0 eV . With higher carrier mobility and better ambipolar dopability, GeO 2 can be a perfect material of choice for homoepitaxially grown p - n junction-based next-generation efficient electronic and optoelectronic devices. , GeO 2 is theoretically anticipated to have a higher intrinsic phonon-limited thermal conductivity (37 W m –1 K –1 along the a direction and 58 W m –1 K –1 along the c direction at 300 K) than others which belong to the same class of UWBG semiconductors . Previous reports have theoretically predicted a high p and n Baliga Figure of Merit for the GeO 2 rutile phase, which can be beneficial while designing power devices with higher block-in voltage with improved on-set carrier conductivity. , Despite the ideal properties for various applications, GeO 2 suffers from the lack in ability to conveniently synthesize nanostructured thin films with a controlled microstructure and crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…17 With higher carrier mobility and better ambipolar dopability, GeO 2 can be a perfect material of choice for homoepitaxially grown p-n junction-based next-generation efficient electronic and optoelectronic devices. 18,19 GeO 2 is theoretically anticipated to have a higher intrinsic phononlimited thermal conductivity (37 W m −1 K −1 along the a direction and 58 W m −1 K −1 along the c direction at 300 K) than others which belong to the same class of UWBG semiconductors. 17 Previous reports have theoretically predicted a high p and n Baliga Figure of Merit for the GeO 2 rutile phase, which can be beneficial while designing power devices with higher block-in voltage with improved on-set carrier conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rutile polymorph has already been proposed as a promising WBG semiconductor [9,75]. Attempts to synthesize thin films of rutile GeO 2 have been difficult due to the existence of competing amorphous and quartz phases [10] and high vapor pressure [11], making our high pressure polymorph a less attractive candidate for further exploration. Cd 2 Ta 2 O 7 is a pyrochlore structure like the identified (III) 2 (IV) 2 O 7 family but using group II and group V elements.…”
Section: Other Candidatesmentioning
confidence: 99%
“…Rutile GeO 2 is recently predicted to be an UWBG semiconductor with high electron mobility, ambipolar doping, and a Baliga FOM that surpasses current technologies [8,9]. However, this performance has yet to be realized in real devices due to difficulty in thin film synthesis [10,11]. Calculations have shown that metastable rocksalt ZnO is ambipolarly dopable unlike its ground state wurtzite version [12], but experiments have yet to realize it.…”
Section: Introductionmentioning
confidence: 99%